The effect of formulation vehicles on the in vitro percutaneous permeation of ibuprofen - Stahl, Jessica (BioMed Central, 2011)
BACKGROUND: The transdermal application of substances represents an elegant approach to overcome side effects related to injections or oral treatment. Due to benefits like a constant plasma level, no pain during application and a simple therapeutic regime, the optimization of formulations for transdermal drug delivery has gained interest in the last decades. Ibuprofen is a non-steroidal anti-inflammatory compound which is nowadays often used transdermally. The objective of this work was to conduct a study on the effect of different 5% ibuprofen containing formulations (Ibutop(® )cream, Ibutop(® )gel, and ibuprofen solution in phosphate buffered saline) on the in vitro-percutaneous permeation of ibuprofen through skin to emphasise the importance of the formulation on percutaneous permeation and skin reservoir. METHODS: The permeation experiments were conducted in Franz-type diffusion cells according to OECD guideline 428 with 2 mg/cm(2 )ibuprofen formulation on each skin sample. Ibuprofen was analysed in the receptor fluid and extracted skin samples by UV-VIS high-performance liquid-chromatography at 238 nm. The plot of the cumulative amount of ibuprofen permeated versus time was employed to calculate the apparent permeability coefficient, the maximum flux and the lagtime, all of which were statistically analysed by One-way ANOVA. RESULTS: Although ibuprofen permeation out of the gel increases rapidly within the first four hours, the cream produced the highest ibuprofen delivery through the skin within 28 hours, followed by the solution and the gel. A significant shorter lagtime was found after gel treatment compared with the cream and the solution. After 28 hours 59% of the applied ibuprofen was found in the receptor fluid of the cream treated samples, 26% in the solution treated samples and 21% in the samples treated with the gel. Fourfold higher ibuprofen reservoirs were found in the solution and gel treated skin samples compared to the cream treated skin samples. CONCLUSION: The present study demonstrates the importance of the formulation on transdermal drug delivery of ibuprofen and emphasises the differences of drug storage within the skin due to the formulation. Thus, it is a mistaken assumption that formulations comprising the same drug amount are equivalent regarding skin permeability.